Genetic tagging in the Anthropocene: scaling ecology from alleles to ecosystems. Issue 4 (26th March 2019) - Lamb, Clayton T.; Ford, Adam T.; Proctor, Michael F.; Royle, J. Andrew; Mowat, Garth; Boutin, Stan
Abstract: The Anthropocene is an era of marked human impact on the world. Quantifying these impacts has become central to understanding the dynamics of coupled human‐natural systems, resource‐dependent livelihoods, and biodiversity conservation. Ecologists are facing growing pressure to quantify the size, distribution, and trajectory of wild populations in a cost‐effective and socially acceptable manner. Genetic tagging, combined with modern computational and genetic analyses, is an under‐utilized tool to meet this demand, especially for wide‐ranging, elusive, sensitive, and low‐density species. Genetic tagging studies are now revealing unprecedented insight into the mechanisms that control the density, trajectory, connectivity, and patterns of human–wildlife interaction for populations over vast spatial extents. Here, we outline the application of, and ecological inferences from, new analytical techniques applied to genetically tagged individuals, contrast this approach with conventional methods, and describe how genetic tagging can be better applied to address outstanding questions in ecology. We provide example analyses using a long‐term genetic tagging dataset of grizzly bears in the Canadian Rockies. The genetic tagging toolbox is a powerful and overlooked ensemble that ecologists and conservation biologists can leverage to generate evidence and meet the challenges of the Anthropocene.